(untitled) (World Bulletin of Social Sciences, 2026)
Learning a language is an emotional process that is intimately related to cognitive growth. The relationship between emotion regulation, resilience, and foreign language anxiety (FLA/FLCA) in second language acquisition (SLA) and positive psychology is examined in this article. It examines how situation-specific anxiety, such as test anxiety, communication anxiety, and fear of receiving a poor grade, limits cognitive resources, lowers engagement, and impedes advancement. On the other hand, the broaden-and-build theory states that positive emotions like foreign language enjoyment (FLE) increase thought-action repertoires, develop linguistic and social resources, and maintain motivation. With its components of self-control, sociability, and empathy, resilience serves as a crucial protective factor that reduces anxiety and promotes greater success. The article emphasizes bidirectional relationships by drawing on five important empirical studies: anxiety mediates the resilience–achievement link to some extent, while mindfulness and resilience together significantly reduce anxiety. Evidence-based strategies for learners and educators are outlined, including low-stakes practice, cognitive reappraisal, mindfulness techniques, growth-mindset activities, reflective journaling, and emotionally safe classroom environments. Technologyenhanced tools and positive psychology interventions are recommended to foster FLE and long-term persistence. Systematic attention to emotional dimensions and resilience-building can transform language learning from a fear-driven process into one of confident, joyful, and effective engagement.